Edukasi Kesehatan Tentang Aktivitas Fisik Dan Gizi Seimbang Selama Pandemi Covid 19 - Qory Jumrotul Aqobah; Annisa Nuradhiani; Masnur Ali (Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Uiveristas Negeri Padang Jl. Prof. Hamka, Air Tawar Padang 25131 Telp. 0751-7059901, 2022)
Community Service Activities (PKM) aim to provide education and training to community members in Kencana Harapan Village, Lebak Wangi District, Serang Regency, especially for people aged 17-55 years regarding the importance of carrying out physical activity and balanced nutritional food during the COVID-19 pandemic in maintaining and improve body health so that people stay fit. The PKM method uses a seminar and training approach. Seminars are conducted by providing knowledge and understanding materials to participants, while the training method is carried out by means of participants and resource persons conducting discussions and simulations. The response given by the service partners was very good, so this service activity could be carried out smoothly with a total of 38 participants. The results obtained, overall the training participants have understood the foods that contain balanced nutrition that are easy and inexpensive that are commonly found, carry out regular physical activities by paying attention to the FITT pattern (Frequency, Intensity, Time, Type).